Sources of financing Islamic commercial banks rise from benefits, costs, opportunities and risks through Sukuk issuance - Oemar, Mogie Demsi; Mubarok, H Jaih; Sanim, Bunasor; Huda, Nurul (Eximia, 2023)
The purpose of this study is to pinpoint many elements that support Sharia Commercial Banks (BUS) in expanding their funding sources. Small capital and limited industrial and individual bank scale are among the problems facing sharia banking, according to the 2015–2019 Sharia Banking Roadmap Guidelines. Out of the 13 BUS, only one fell into the BUKU 3 category (capital IDR 5-30 trillion) in terms of capital as of December 2016. Compared to conventional banks, which have 32,730 office units, Islamic banks only have 2,201 office units. This makes it harder for sharia banks to collect deposits from the general population. This suggests that there are funding source issues for Islamic banking as well. Due to a lack of funding, the duty of intermediary cannot be performed as effectively as possible. Sukuk issuing is one way that sharia banking might enhance financial sources. It is vital to take into account the advantages, possibilities, costs, and dangers when issuing sukuk in order to develop a suitable plan for funding increases. The following are contributing aspects to the advantages of issuing sukuk: a source of financing for business expansion; market analysis and sharia benchmarks; many contracts, coupons, and periods; and enhanced liquidity, efficiency, and profitability. Sub-factors for opportunity include: few issuers; high investor demand; robust regulatory backing; and a large investment base. Cost sub-factors include guarantee fees, emission charges, capital expenses, and loan costs. Sub-risk elements include interest rate risk, default risk, sharia compliance risk, and asset loss risk.